Analysis temporary space (1981-2010) of the precipitation in the city of Bogota: advances in the generation of extreme indices - Aragón-Moreno, Juan Antonio; Lerma-Lerma, Brayan David (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The investigation analyzed the spatial and temporal scenarios of extreme precipitation events in Bogotá, Colombia, based on the development of climate end indexes endorsed by the Intergovernmental Panel on Climate Change (IPCC) and their capacity to predict climate trends. Data of daily frequency and records of thirty years of 23 meteorological stations distributed widely in the city were worked, in order to provide the greatest amount of spatial information. The quality and absence of data were controlled. The climatological profile revealed two monthly rainfall regimes in the study area with values ​​of up to 87.2 mm / day of precipitation, in addition two broad areas of precipitation convergence were found. The indexes showed a positive regional trend except in the south of the city where negative trends were presented, which projected notable changes in the intensity, duration and frequency of extreme events, in the same way the geostatistical analysis detailed the eastern area with a wide nuance in hydrological dynamics, appropriate to be explored in future research. Ultimately, this research is aimed at expanding and disseminating key information in the planning and planning of the territory, as well as in the prevention and management of risk in the face of extreme weather scenarios such as landslides, floods or droughts in cities located by above 2000 m.a.s.l. and in this way help decision makers, researchers, professors and university students to use an internationally approved methodology that unifies criteria for the collation of climate information.